Η γυναικεία παραδοσιακή φορεσιά από τον Σοχό Θεσσαλονίκης - Αγτζίδου, Ευθυμία (Μακεδονικά, 2011)
The study concerns the traditional female costume of Sochos, a village onthe borders of the Thessaloniki and Serres prefectures. The majority of theinhabitans of Sochos were natives, while the minority were refugees from thePontos region, as well as a few Vlach families. The inhabitans dealt with livestock breeding, agriculture and trade. They got along well with the inhabitantsof Ossa, a village near the town of Lagadas, and mostly with the inhabitants ofNigrita, a village in the Serres prefecture with which they shared similarities incustoms, traditions and costumes.The study was based on field work carried out in Sochos and in the cityof Thessaloniki, where a large group of inhabitants of Sochos settled down inthe 60’s and 70’s. The goal of this study was to record the female costume ofSochos, as it is a subject lacking bibliography citations.The female costume, as described, was worn from 1920 up to 1970. Thestudy is divided in two units. In the first unit the main parts of the costume arethoroughly described, in the sequence they were put on, starting with theunderwear and reaching even jewelry. Moreover, in the cases where enoughproof could be gathered, parts of the female costume of older times arepresented (before 1920).The second unit refers to the bridal costume, known as «Gerakina». Itwas worn according to the type described up to 1930/5. The bridal costume’sparts are analyzed in every possible detail and the changes that have takenplace after 1935 are located.